Male Germ Line Development in Arabidopsis. duo pollen Mutants Reveal Gametophytic Regulators of Generative Cell Cycle Progression - Durbarry, Anjusha (American Society of Plant Biologists, 2005)
Male germ line development in flowering plants is initiated with the formation of the generative cell that is the progenitor of the two sperm cells. While structural features of the generative cell are well documented, genetic programs required for generative cell cycle progression are unknown. We describe two novel Arabidopsis (Arabidopsis thaliana) mutants, duo pollen1 (duo1) and duo pollen2 (duo2), in which generative cell division is blocked, resulting in the formation of bicellular pollen grains at anthesis. duo1 and duo2 map to different chromosomes and act gametophytically in a male-specific manner. Both duo mutants progress normally through the first haploid division at pollen mitosis I (PMI) but fail at distinct stages of the generative cell cycle. Mutant generative cells in duo1 pollen fail to enter mitosis at G2-M transition, whereas mutant generative cells in duo2 enter PMII but arrest at prometaphase. In wild-type plants, generative and sperm nuclei enter S phase soon after inception, implying that male gametic cells follow a simple S to M cycle. Mutant generative nuclei in duo1 complete DNA synthesis but bypass PMII and enter an endocycle during pollen maturation. However, mutant generative nuclei in duo2 arrest in prometaphase of PMII with a 2C DNA content. Our results identify two essential gametophytic loci required for progression through different phases of the generative cell cycle, providing the first evidence to our knowledge for genetic regulators of male germ line development in flowering plants.